10-minute consultation Morbilliform rash (BMJ Publishing Group, 2004)
Address the parents’ concerns about meningitis—A nonblanching rash may be a crucial sign, but in the evolving stages of meningococcal disease the rash may be blanching and maculopapular. Other important features in recognising meningococcal disease are poor eye contact, irritability, lethargy and lack of interest, vomiting, stiffness in the neck (though this may not be seen in infants), pallor, tachycardia, and prolonged capillary refill. History of symptoms—Ask about the duration and height of the fever and the sequence of fever and rash development. A rash that appears as the fever resolves is typical of roseola infantum. In erythema infectiosum “slapped cheeks” and a lace-like rash may occur up to a week after fever. Vaccination history—Having had a measles, mumps, and rubella (MMR) vaccination makes a diagnosis of measles or rubella less likely but does not exclude it. The rash may be due to a recent MMR vaccination. Contact history—Is there a history of recent contact with another child with a fever or rash? Which infectious diseases are common in the local community? Local and national surveillance information may help in making a diagnosis. Ask about any close contact with a pregnant woman. Rubella and parvovirus B19 (which causes erythema infectiosum) may damage an unborn child. Enteroviruses and adenoviruses (respiratory infection) are other viral causes of rashes. Also take a travel history and consider relevant diseases. Measles is endemic in many parts of the developing world. Mediterranean spotted fever leads to fever, rash, and a necrotic area (eschar) at the site of the tick bite.